Recalling the Future of ACC - Gaskins, Richard (Victoria University of Wellington Law Review, 2000)
Richard Gaskins visited the Law Faculty as a Fulbright from January to August 1999 to study developments in the Accident Compensation regime. His visit coincided with the controversy surrounding the National Government’s Accident Insurance Act 1998. Professor Gaskins gave the following paper, in which he addresses the continued importance of the Woodhouse Report, at a seminar on Accident Compensation held as part of the 1999 Australasian Law Teachers' Association Conference. In the paper he highlights two important insights of the Woodhouse Report that he believes have lasting value: its linking of tort reform to social welfare and its promotion of an ecological approach to preventing accidents. Professor Gaskins concludes that both insights retain their importance and challenges legal academics to address them as well as the more narrowly based law and economic approach to accidents that has dominated legal policy and academic thought since the early 1970s.